Posterior Reversible Encephalopathy Syndrome as Presenting Form of Very Early Systemic Sclerosis - María Isabel Pedraza; Julia Barbado; Marina Ruiz; Ángel Luis Guerrero (Case Reports in Neurological Medicine)
Introduction. Posterior Reversible Encephalopathy Syndrome (PRES) is an increasingly recognized clinical and radiological entity with a wide spectrum of symptoms. Its mechanism depends on failure of the blood-brain barrier due to high systemic blood pressure (BP) and loss of integrity of vascular endothelium related with different triggers. Methods. We aim to report a case of PRES induced by arterial hypertension and very early systemic sclerosis (SSc) not previously known. Results. A 64-year-old female was admitted due to 1-week pulsating headache more prominent on frontal scalp, accompanied by phonophobia, photophobia, and facial flushing. Neurological exam revealed brisk deep tendon reflex. Brain magnetic resonance imaging (MRI) showed subcortical lesions mainly located in posterior regions. BP was monitored and episodic arterial hypertension was detected. In laboratory tests positive anti-topoisomerase I antibodies were detected. BP was controlled with angiotensin-converting-enzyme inhibitors and headache improved. In a new MRI a month later improvement of white matter lesions was observed. Capillaroscopy showed “active pattern,” considered typical of SSc. Conclusion. In SSc anti-endothelial cell antibodies impair vascular endothelium and liberation of vasoconstrictors leads to BP increasing and disruption of blood-brain barrier autoregulation mechanisms. PRES can be the first manifestation of very early SSc and this entity should be considered even in absence of skin lesions or Raynaud phenomenon.